Risk factors of long-term sickness absence in Norway and Sweden - Vegard Johansen (Nordic Journal of Social Research, 2013)
Aims: This paper examines the level of long-term sickness absence (LTSA) in Norway and Sweden. It also investigates whether risk factors of LTSA are the same in Norway and Sweden. Methods: More than 2500 Norwegian and Swedish workers between 20 and 60 years of age answered a postal questionnaire. The Norwegian and Swedish samples are weighted and representative with regard to regional background variables and demographic background variables, but the response rate was low. LTSA is defined as 15 days or more sickness absence in the previous year. Binary logistic regression is used to detect which factors influence LTSA. The analyses of LTSA include demographic factors, socio-economic position, and occupational characteristics.